Change Management and the Human Factor : Advances, Challenges and Contradictions in Organizational Development - Dievernich, Frank E. P.; Tokarski, Kim Oliver; Gong, Jie (Springer International Publishing : Imprint: Springer, 2015)
Change management and organizational development is unthinkable without people. Human beings form its core as both subjects and objects of change. This volume attempts to cut through to the core of change management, to the people that stand at its heart and focuses on their intrinsic role in change management and organizational development. Topics covered in this volume encompass the human element within organizational change, how this impacts roles, dynamics of team interaction and affects the workplace in teaching and learning settings. It also addresses resistance to institutional and organizational change and the central role that agile management plays in this process.